Community based household data collection in a post pandemic world-challenges and way forward - Rajput, Mansi; Premjit, Reesha; Bhagat, Shambhavi; Singh, Ranjana; Ray, Shomik (International Journal Of Community Medicine And Public Health, 2024)
The COVID pandemic has instilled fear in the community creating challenges for household data collection. A community-based household survey was planned to assess knowledge and perception about air pollution caused by vehicular traffic and related ailments among residents of Delhi along with willingness to accept (WTA)/willingness to pay (WTP) discount/premium to discontinue/continue the use of private vehicles for their daily office commute. Access into households was difficult due to heightened sensitivity in post COVID situation. Respondents were not available during working hours. Researchers reached out to participants at workplaces, community events, during weekends or after office hours. Safety of researchers due to odd working hours was a concern. Researchers in post-pandemic world need to plan for multiple modes to access participants. Timelines of the data collection phase need to be sensitive for higher proportion of refusals and necessary permissions. Higher investments in effective communication skills are necessary.